Four plasmid genes are required for colicin V synthesis, export, and immunity. - Gilson, L (1987)
The colicin V production and immunity genes were isolated from plasmid pColV-K30. A HindIII-to-SalI fragment of 9.4 kilobases was cloned into the compatible vectors pBR322 and pACYC184. Mutants defective in colicin production were generated by Tn5 insertions and by constructing deletions in vitro. Physical analysis of these mutations identified a 4.4-kilobase region of this DNA which contains all the plasmid genes (cva) needed for the production of colicin V. The colicin V immunity determinant (cvi) is in a 700-base-pair fragment located within one end of this region. Complementation tests identified three genes, called cvaA, cvaB, and cvaC, required for colicin production. Analysis of the proteins labeled in minicells harboring various Tn5 insertions allowed us to identify protein products for the cvaA and cvaC genes. Mutations in cvaA and cvaB eliminated colicin activity in culture supernatants, but not within the cells. Mutations in cvaC, however, eliminated all detectable activity. From these results we conclude that the cvaC gene codes for the structural gene for colicin V, while cvaA and cvaB are apparently needed for the normal export of the colicin.